FINANCIAL PERFORMANCE ASSESSMENT AND TAXPAYER COMPLIANCE TEST IN USING TOTAL BENCHMARKING AT PHARMACEUTICAL COMPANIES - Widi Dwi Ernawati (Master of Accounting Universitas Trunojoyo Madura, 2017)
This study aims to:1) to determine whether there is a difference between the ratio of pharmaceutical companies from 2011-2015 with the total benchmarking ratio established by the Directorate General of Taxes; 2) to know the total use of benchmarking ratio in testing taxpayer compliance. The sample used is the annual report of 7 pharmaceutical companies listed in Indonesia Stock Exchange (BEI) for the period of 2011 - 2015. Data analysis in this study was conducted by: 1) Calculated the average of 12 ratios, i.e GPM, OPM, PPM, CCTOR, NPM, DPR, salary, lease, depreciation, other input ratios, non-operating income ratio, and off-business cost ratio; 2) Identified the difference of each ratio with benchmarking ratio by using Independent Test Sample T-test; 3) Analyzed the ratios below and above the total benchmarking ratio; 4) Used the Total Benchmarking Ratio to detect Tax Evasion. The results show the ratio of GPM, OPM, PPM, NPM, salary, rent, and other inputs, different not significant. While the ratio of CCTOR, DPR, depreciation, non-business income and non-business costs, is significantly different from the total benchmarking ratio. The use of benchmarking ratios to test taxpayer compliance resulted in recommendations to focus further analysis on accounts relating to material purchases and use, as well as non-business income and expenses.